To Study the Frequency of Acute Rejections in Renal Transplant Recipients on Cyclosporine Regimen within 3 Months’ Post-transplant at a Renal Care Setup - Rida Malik, Mishal Haroon, Natasha Khatri, Sajid Sultan, Mehreen Mujahid, Aasim Ahmed, Murtaza Dhrolia (Pakistan Journal of Medical & Health Sciences, 2024)
Background: One of the primary causes of early graft dysfunction after renal transplantation is still acute rejection, especially in the first three months after the procedure. Objective: To study the frequency of acute rejections in renal transplant recipients on a cyclosporine-based immunosuppressive regimen within three months post-transplant at a renal care setup. Methodology: This descriptive study was conducted at The Kidney Centre Post Graduate Training Institute (TKC PGTI), Karachi, over six months from August 2020 to February 2021. Using successive sampling, 30 renal transplant patients between the ages of 18 and 65 who were taking cyclosporine (4.5 mg/kg/day) in addition to mycophenolate mofetil and prednisolone were included. In order to assess graft function, blood creatinine levels and cyclosporine C0 and C2 levels were tracked on Days 3 and 9. SPSS v20 was used to analyze the data, and p < 0.05 was considered statistically significant. Results: Eleven (36.67%) of the thirty patients had acute rejection in less than three months. Most were between the ages of 18 and 40 (n=23, 76.67%) and male (n=21, 70.00%). On Day 3, the mean cyclosporine C2 level was 1065.1 ± 414.98 ng/mL, and on Day 9, the mean C0 level was 220.06 ± 260.53 ng/mL. On Day 9, the mean serum creatinine was 1.23 ± 0.79 mg/dL, down from 1.56 ± 0.94 mg/dL on Day 3. The only factor that was substantially linked to acute rejection was age (p = 0.02). Conclusion: Despite therapeutic cyclosporine levels, acute rejection occurred in over one-third of patients, especially among younger recipients, highlighting the need for tailored immunosuppression and close monitoring. Keywords: Renal transplantation, acute rejection, cyclosporine, immunosuppression, graft function